Evaluation of Antimalarial Drug use in Tertiary Care Teaching Hospital - Deshpande, Anushree Shrikant; Shalavadi, Mallappa Hanamantappa; Patel, Harshitkumar Bhupendrabhai; Vasoya, Arvind Dayalbhai; Kotwal, Rahul; VM, Chandrashekhar (Indian Journal of Pharmacy Practice)
Background: Malaria is a major cause of morbidity and mortality in the developing countries. Rational use of antimalarial drugs reduces the development of drug resistance and cost of therapy. Hence, we sought to evaluate the use of antimalarial drugs. Aim: The study was designed to evaluate the use of anti-malarial drugs in in-patient admission of medicine and pediatrics department at tertiary care teaching hospital. Methods: The data was obtained prospectively from 98 patients with antimalarial drugs over a period of 6 months. The evaluation was assessed based on age, pattern of malarial parasite, therapy and rationality of prescription. Results: The demographic details of patients admitted in hospital showed more male patients (60.52%) than children’s (19.48%) and this reflects that the prevalence of the disease was higher among adult patients in this region during the study. Out of 98 patients prescribed with antimalarial drugs, only 46 patients showed malarial infection and 52 patients were diagnosed with non-malarial infection. In this study three drug combination therapy was prescribed more (30.61%) followed by two drugs combination. Rationality of antimalarial drug prescription was assessed by NVBDCP out of which 45.65% and 82.69% were irrational respectively. Conclusion: In this study it was found that inappropriate use of antimalarial drugs was higher among patients with Plasmodium falciparum and non-malarial patients. Cost of therapy was very high and thus it contributed to the economic burden on patients. Irrational prescriptions were high which indicated non-adherence to guidelines. Hence it concludes that educating the health professional for rational drug use as well as reducing the cost of therapy is essential.
Keywords: Antimalarial; Rationality; Drug interaction; Cost effective analysis